Pendampingan Pemanfaatan Sumber Daya Lokal Untuk Meningkatkan Ekonomi Lokal - Rismayani -; Baiq Harly widayanti; Furqonnur Fitra; Langgamada Tri Ovanda; M.; Sri Wahyuningsih (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
Pengenjek village has the potential for local resources in the form of ijuk from enau trees. Currently, the ijuk produced from this enau tree after drying is directly sold without further processing. The making of ijuk is used as a source of livelihood for the people in Pengenjek Village. The magnitude of this potential can be developed into various products that have a higher selling value. So by seeing this potential, the purpose of this service is to utilize the potential of local resources to become potted plants so that they have a higher selling value. The method used is to provide practical mentoring in the manufacture of products made from ijuk. This mentoring activity for the use of ijuk is carried out for 1 week starting from the preparation of materials to the practice of making them. The target of the activity is a group of women in Pengenjek Village, both adolescents and adults. As a result of this activity, the community's skills in processing ijuk into more useful and higher-value goods increased. It is hoped that with the products produced having a high selling value, the income of the people of Pengenjek Village will increase so that the level of welfare of the community can increase.